Study of the Main Causes of Early Postoperative Mortality after Surgical Interventions on the Mitral Valve on the Background of Infective Endocarditis - Soltani, Suzanna E.; Babochkina, Alisa R. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the structural and functional changes of the mitral valve (MV) in patients with infective endocarditis, taking into account demographic differences that may affect early postoperative mortality. Materials and methods. The study included patients (n = 107) with a history of infective endocarditis with the MV damage. All the patients underwent surgical treatment taking into account the functional lesions of the MV. The material for the analysis was the data from medical records, findings of physical, clinical and instrumental examination, and the operation report. The patients were divided into two study groups: experimental group (n = 67) with the subjects who underwent MV repair, and control group (n = 40) with those who underwent MV replacement. Results. Analysis of gender-specific length of hospital stay showed that deceased male patients were treated for significantly less time compared to those who survived: 3.5 vs. 13.4 bed days (p = 0.02, χ2= 5.12). Assessment of length of stay in the intensive care unit (ICU) showed that deceased patients of experimental group stayed in the ICU significantly longer than those who survived: 14.2 vs. 4.2 bed days (p = 0.02, χ2= 4.85). It was established that there was a significant difference in gender-specific length of stay in the ICU: in male patients of experimental group (p = 0.03, χ2= 4.55) and in women of experimental group (p = 0.02, χ2= 5.24). It was found that deceased patients from the experimental group stayed in the ICU significantly longer compared to similar patients from the control group: 14.2 vs. 4.0 bed days (p = 0.02, χ2= 5.12). Among patients who died, the frequency of urgent operations was significantly higher than in those who survived: 28.6% vs. 12.0% (p = 0.006, χ2= 7.52). The frequency of scheduled operations in control group was significantly higher than that of urgent operations: 92.5% vs. 7.5% (p = 0.04, χ2= 3.98). The incidence of severe MV insufficiency was significantly higher in female patients of the experimental group who were discharged for rehabilitation compared to those in the control group: 100.0% vs. 62.5% (p = 0.02, χ2= 5.47). Conclusions. When analyzing the structural and functional changes in the mitral valve that could cause early post-operative mortality, it was found that severe mitral insufficiency was the most common (93.5%). It was established that mitral valve damage by massive vegetations with the threat of detachment was 57.0%. It was found that mitral valve abscesses were absent in 77.6% of patients, and among deceased patients they were not detected at all. Reliable features of providing qualified care to patients with MV lesions against the background of infective endocarditis are established; these are related to the duration of inpatient treatment, stay in the ICU, and urgency of surgical interventions.